Implementasi Kebijakan Diklat Struktural Pim III Pada Dinas Pariwisata Dan Olahraga Kabupaten Batu Bara - Khaira Nurul Atiah; Badaruddin Badaruddin; Nina Siti Salmaniah Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The article aims to find out that tourism management in Batu Bara Regency needs serious attention from the local government, considering that the potential of natural resources in Batu Bara Regency is also not comparable to the abundant natural wealth potential of other regions in North Sumatra. This qualitative approach is used to find and understand what is hidden behind phenomena which are sometimes difficult to know or understand, this approach is also expected to be able to provide a complete and detailed explanation of the phenomena that are the focus of the author's research. The results of the study show that the policies provided by PIM III Alumni in terms of communication are that after the Diklatpim, PIM III Alumni are able to carry out policies in terms of communication, namely forming new innovations in the form of a Tourism Awareness Group Program for the community according to tourism locations in the Batu Bara Regency. The task of the Tourism Awareness Group is to introduce the wider community to the tourism sector so that tourism is able to compete with other tourism in North Sumatra.